Intention to adopt web-based halal traceability system among small and medium enterprises of food sub-sector in Peninsular Malaysia - Muhamad, Nur Aminin (2020)
Food fraud especially in halal food products caused the biggest concern among Muslim consumers to arise that need consideration by the food manufacturers specifically small and medium enterprises (SMEs). Traceability system could improve the halal transparency along the food supply chain. The Department of Islamic Development Malaysia (JAKIM) had introduced Halal Assurance Management System (HAS) as a guideline for halal traceability system, however, only multinational and medium companies are required to comply with this guideline. Moreover, the adoption of sophisticated systems among SMEs in Malaysia is still low. This could lead to their reluctance to adopt web-based halal traceability system. The general objective of this study was to identify the intention to adopt web-based halal traceability system among SMEs of food sub-sector in Peninsular Malaysia. Five specific objectives of this study were to determine the level of intention to adopt web-based halal traceability system among SMEs of food sub-sector in Peninsular Malaysia; to determine the association between firmographic profiles of SMEs of food sub-sector in Peninsular Malaysia and their intention to adopt web-based halal traceability system; to identify the relationship between the factors towards perceived usefulness of web-based halal traceability system and perceived ease of use of web-based halal traceability system; to identify the most influential factors that influence the intention to adopt web-based halal traceability system among SMEs of food sub-sector in Peninsular Malaysia; and to suggest possible policy recommendations towards adoption of web-based halal traceability system in Malaysia’s halal industry. An interviewer-administered questionnaire was used for data collection of 260 halal-certified food SMEs that were selected using a systematic random sampling method. The data were analyzed using descriptive analysis, mean ranking analysis, Chi-square analysis, Pearson correlation analysis, and logistic regression analysis. Most of the respondents were from middle-level management (95 respondents, 36.5%). The majority of food SMEs involved in this study (207 companies, 79.6%) were small business size companies. This study revealed the utilization of information and communication technology (ICT) tools especially the advanced system by the food SMEs was still low. The majority of food SMEs showed a high intention to adopt web-based halal traceability system. Sales turnover and region have a significant association with intention to adopt web-based halal traceability system among food SMEs. Besides, the environmental aspect and perceived usefulness of web-based halal traceability system showed a strong correlation (r=0.720, p<0.01). Logistic regression analysis revealed that perceived usefulness, perceived ease of use, and sales turnover were the influential factors of intention to adopt web-based halal traceability system among food SMEs. This study recommends JAKIM to enhance the effectiveness of HAS by guiding the micro and small size SMEs to implement HAS in their business operations. Food SMEs that faced financial constraints are encouraged to seek financial schemes provided by responsible authorities. Besides, network coverage needs improvement throughout the region, especially in rural areas. The number of events for participation of food SMEs need to be intensified to trigger their competitive spirit and innovativeness in improving their business performance. The course and training on halal traceability system are needed for the enhancement of knowledge and skills about the system.